Knowledge Based Information System for Strengthening the Competitive Advantages of Women Technopreneurs in Malaysia - Fuad, Nurwahida (Information Management and Business Review, 2013)
In context of technopreneur business, competitive advantages is the top most issues that facing by women entrepreneurs especially for sustaining their market position and profitability. The dramatically change of technopreneur landscape has exposed the women technopreneur with some of global challenges. In the one hand, competitive advantages possible to transform the business into the best track by monitoring the rapid change of external and internal environment of business. However, in the one hand, competitive advantages have exposed the business to some risks, damage and negative impacts if they are not ready to adopt the suitable strategy. The main objective of the paper is to discuss the competitive advantages forces of women technopreneur firms. Secondly, the paper is aimed to highlight the usability of knowledge based information system (KBIS) in dealing with the main issues of competitive advantages. This study has adopted the model of Porter Five Forces by Michael Porter to understand the competitive advantages as faced by women technopreneur. Meanwhile, the potential use of KBIS will explored by conducting the unstructured interview with selected expertise. In the turbulences market environment, KBIS should integrate with strategy which can help women technopreneur firms to positioning them self into the right time and track. Finally, some suggestion was made to guiding women technopreneur in integrating KBIS sophistication with strategy options as a new way of advancement.